ANALISIS KEPUASAN PENGGUNA TERHADAP PORTAL FUN STUDY MENGGUNAKAN MODEL DELONE & MCLEAN - Wulandari, Wulandari; Heksaputra, Dadang; Wicaksono, Yanuar; Ratnasari, Asti (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
Fun study is a web-based information system as a training center. Fun study is an online portal. Fun study is designed by jogja tourism training center in yogyakarta. The fun study aims to develop the skills and competence of human resources. Some users have difficulty accessing and are unfamiliar with the menus on the fun study. No quick measurement of effectiveness, user satisfaction, and any successful fun study on users so far. Hence, it aims to measure systems against users. The system measures can be taken using a delone & McLean model. The data collection technique in this study is from a questionnaire with a population in the sleman region. Sampling sampling uses only 96 people who use portal fun study. Research tested using smartpls software suggests that the delone & McLean model has not been able to assess fun study users' satisfactio. This is proved by hypothetical testing, of the nine hypotheses that were formulated there were 4 hypotheses received and 5 hypotheses not received. It could be concluded that the quality of services, the quality of systems and users significantly affected. Whereas user satisfaction significantly affects user satisfaction.